Kepercayaan Pelanggan, Kemudahan dalam Bertransaksi dan Harga Produk terhadap Keputusan Berbelanja Online - Alvin Luhur; Hendra Jonathan Sibarani; Jhansen Salim; Jefri Jefri (Journal of Management and Bussines (JOMB), 2023)
This study aims to determine the effect of customer trust, ease of transaction, and product prices on online shopping decisions on the Tokopedia application. This research method is descriptive quantitative. The research instrument used a questionnaire which was distributed online to 100 respondents in Medan-Kota District. Data analysis techniques to test the hypothesis using Structural Equation Modeling (SEM) based on a variant called Partial Least Square (PLS) and the SmartPLS application version 3.0 as a tool to analyze it. The results showed, a) the variable customer trust in online shopping decisions has a t statistic value of 4,529 > t table of 1,985 and obtains a P-value of 0.000 <0.10; b) the variable of ease of transaction on online shopping decisions has a statistical t value of 1,805 < t table of 1,985 and obtains a P-value of 0.072 < 0.10; c) the product price variable on online shopping decisions has a statistical t value of 4,670 > t table of 1,985 and obtains a P-value of 0.000 <0.10. In conclusion, customer trust and product prices have a positive and significant effect on online shopping decisions on the Tokopedia Application. However, the convenience of transactions does not affect online shopping decisions on the Tokopedia application. Keywords: Product Prices, Ease of Transactions, Customer Trust, Online Shopping Decisions